Under-exposure to official matches is associated with muscle injury incidence in professional footballers - Moreno-Perez, V.; Paredes, V.; Pastor, D.; Garrosa, F.; Vielcazat, S.; Coso, J.; Mendez-Villanueva, A. (Biology of Sport, 2021)
External workload from matches is considered one of the most important muscle injury risk factors for football teams. However, there is scarce published evidence to support this belief. This study examined whether a particular profile of external match workload existed prior to a muscle injury. A total of 144 professional football players belonging to 2 teams were monitored over three seasons. For each muscle injury, a profile of external workload variables was determined for 5 to 8 games and expressed as: time playing exposure, total distance (TD) covered and high-speed running (HSR) covered. In addition, acute:chronic workload ratio (ACWR) was calculated. Sixty players (41.6%) reported a total of 86 muscle injuries during the three seasons. Muscle injuries occurred principally in matches (79.1%), the hamstring being the most affected muscle (44.1%). Injured players displayed substantially lower accumulated exposure time (ES = 0.45), TD (ES = 0.45) and HSR (ES = 0.39) in comparison with uninjured players in the last 5 games prior to injury. Compared to the uninjured players, ACWR for exposure (ES = -0.29/0.02) and running load (ES = -0.24/0.00) did not differ between match 5 and 2 prior to the injury, although uninjured players displayed a substantially greater ACWR in all 3 variables (ES = 0.31/0.35) than injured players in match 1 prior to the injury. Lower playing exposure (minutes played) and associated reduced running distances (TD and HSR) were observed in injured football players. Being underloaded in official games could be a mediator for muscle injury in this cohort of elite football players.